Description of a new Ornithodoros (Pavlovskyella) (Ixodida: Argasidae) tick species from Pakistan - Abid Ali; Mehran Khan; Muhammad Numan; Abdulaziz Alouffi; Mashal M. Almutairi; Ronel Pienaar; Minique H. de Castro; Lidia Chitimia-Dobler; Sebastián Muñoz-Leal; Ben J. Mans; Ala Tabor (Parasitology)
The genus Ornithodoros is notably diverse within the family Argasidae, comprising approximately 134 species distributed among 4 subgenera, 1 of which is the subgenus Pavlovskyella. In an earlier study, we identified distinct soft ticks as Ornithodoros (Pavlovskyella) sp., which were collected from animal shelters in Khyber Pakhtunkhwa, Pakistan. Providing additional collections from that same locality and a comprehensive analysis involving detailed morphological and mitogenome-based comparisons with closely related species, this study formally designates a novel species for these specimens. Adults and late-instar nymphs of the new species display a dorsoventral groove, small cheeks not covering the capitulum, 5 small even humps on tarsus I and a transverse postanal groove intersecting the median postanal groove perpendicularly. It also lacks a tuft of setae on the ventral surface of the hood which separates the novel species from Ornithodoros papillipes. Ventral chaetotaxy of tarsus IV indicates 4–7 setal pairs in nymphs and 5–7 pairs in adults that separate the new species from Ornithodoros tholozani sensu stricto and Ornithodoros crossi, 2 morphologically closely related species that occur in geographical proximity. Phylogenetic analyses of the full-length mitochondrial genome and the 18S and 28S ribosomal RNA genes, combined with pairwise nucleotide comparisons of cox1, cox2, atp8, atp6, cox3, nad3, nad5, nad4, nad4L, nad6, cytb, nad1, nad2, 12S rDNA, 16S rDNA, 18S rDNA and 28S rDNA further support that the new species belongs to the Pavlovskyella subgenus, clustering with O. tholozani, Ornithodoros verrucosus and Ornithodoros tartakovskyi.